Bargaining Power Health Policymaking from England and New Zealand - Smith, Verna (Springer Singapore, 2018)
This monograph applies Kingdon's Multiple Streams Framework to two policymaking episodes of implementing pay for performance in general practice, conducted in England and New Zealand. The Framework's explanatory power for policymaking in Westminster majoritarian jurisdictions is tested and, based on rigorous comparative analysis, recommendations are made for its refinement. The monograph also offers striking lessons for policymakers about how to negotiate successfully with general practitioners. .